Content Creator Strategy as Tourism Journalism for Post-Covid-19 Pandemic Recovery - Wiksana, Wiki Angga; Firmansyah; Putri, Dian Widya; Cakranegara, Doddy Iskandar (UPT Publikasi Ilmiah UNISBA, 2023)
Pikiran Rakyat Media Networks (PRMN) engaged in the digital media business, develops its business by creating a media ecosystem through multiple portals. The PRMN sub-domain news portal is managed and filled with content by content creators as PRMN partners. The phenomenon of content creators on news portals creates opportunities for strategies in tourism recovery. This research was conducted with the aim of looking at strategies for utilizing content creators as a form of journalism to advocate for tourism recovery in Indonesia. This study aims to get an overview of tourism journalism patterns carried out by content creators which can be a strategy for recovery and increasing the attractiveness of tourist destinations. This study uses a constructivist approach by finding qualitative data to be analyzed and categorized so that it becomes a pattern of tourism communication through journalism in digital media. The results of the study show that the strategy to restore the tourism sector after the Covid-19 pandemic requires the role of mass media and social media. The collaboration business strategy carried out by PRMN with the google algorithm supports the creation of positive tourism content in marketing tourist destinations according to tourist targets.